IMPLEMENTASI ADVOKASI BERBASIS KOMUNITAS DALAM PENANGANAN KEKERASAN SEKSUAL ANAK: STUDI PERAN KPAID KABUPATEN TASIKMALAYA - Fauziah, Sofiatul; Marwah Insani, Hakimah (Siyasyatuna | Jurnal Hukum Tata Negara, 2025)
This study examines the role of the Regional Indonesian Child Protection Commission (KPAID) of Tasikmalaya Regency in advocating for cases of child sexual abuse. The study is motivated by the increasing number of child abuse cases, which remain a serious issue in Indonesia. The purpose of this research is to identify the factors that cause child sexual abuse, the forms of advocacy conducted by KPAID, and the number of cases recorded in 2023. The research employs a qualitative approach through literature review and field research. The findings show that the causes of child sexual abuse include parenting patterns, the influence of social media, lack of education, and economic factors. KPAID’s advocacy efforts include psychological support, legal assistance, fulfillment of the right to education, and trauma recovery measures. There were 17 recorded cases of child sexual abuse from January to September 2023, with victims aged between 10 and 17 years.